2016
DOI: 10.1063/1.4941971
|View full text |Cite
|
Sign up to set email alerts
|

Direct excitation of TE11 mode in a relativistic backward wave oscillator

Abstract: A relativistic backward wave oscillator for directly generating TE11 mode is proposed. An axially asymmetric slow wave structure and a sectioned annular cathode are introduced to suppress the TM01 mode and excite the TE11 mode. A pre-modulation dual-cavity, which allows part of the backward power to propagate into the diode region, is adopted to optimize the electron beam bunch, indicating that the conventional design principle that the diode region and the beam-wave interaction region should be isolated can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A relativistic backward wave oscillator (RBWO) has become one of the most popular high-power microwave (HPM) sources, owing to its remarkable operating stability, high output power, and high repetition rate [1][2][3][4][5][6][7][8][9][10][11]. Generally, an RBWO operates in either the symmetric TM 01 mode or the TEM mode [3,[12][13][14]. However, these modes are unsuitable for direct radiation because of their doughnut-shaped radiation patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A relativistic backward wave oscillator (RBWO) has become one of the most popular high-power microwave (HPM) sources, owing to its remarkable operating stability, high output power, and high repetition rate [1][2][3][4][5][6][7][8][9][10][11]. Generally, an RBWO operates in either the symmetric TM 01 mode or the TEM mode [3,[12][13][14]. However, these modes are unsuitable for direct radiation because of their doughnut-shaped radiation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al presented an RBWO that directly generated a linearly polarized TE 11 mode by using an asymmetric slow-wave structure and a sectioned annular cathode [12]. But, undesired electron movement in the azimuthal direction will result in parasitic mode generation, which increases with time gradually.…”
Section: Introductionmentioning
confidence: 99%
“…In the explosive electron emission (EEE) process of the EECs, 3,4 the EEE nonuniformity is unavoidable due to the cathode surface morphology, which may result in the excitation of asymmetric modes or mode competition. 5 The nonuniformity of the EEE lies in the explosions of the micropoints in the cathode surface and the subsequent formation of the cathode plasma. Experiments have confirmed that only a few of initial emission micropoints explode in the cathode surface, thereafter, the emission micropoints will decrease the electric field in vicinity, preventing other micropoints from emitting electrons.…”
Section: Introductionmentioning
confidence: 99%